Anxiolytic and antidepressant profile of the methanolic extract of Piper nigrum fruits in beta-amyloid (1–42) rat model of Alzheimer’s disease - Hritcu, Lucian (Behav Brain Funct, 2015)
BACKGROUND: Piper nigrum L. (Piperaceae) is employed in traditional medicine of many countries as analgesic, antiinflammatory, anticonvulsant, antioxidant, antidepressant and cognitive-enhancing agent. This study was undertaken in order to evaluate the possible anxiolytic, antidepressant and antioxidant properties of the methanolic extract of Piper nigrum fruits in beta-amyloid (1–42) rat model of Alzheimer’s disease. METHODS: The anxiolytic- and antidepressant-like effects of the methanolic extract were studied by means of in vivo (elevated plus-maze and forced swimming tests) approaches. Also, the antioxidant activity in the amygdala was assessed using superoxide dismutase, glutathione peroxidase and catalase specific activities, the total content of the reduced glutathione, protein carbonyl and malondialdehyde levels. Statistical analyses were performed using one-way analysis of variance (ANOVA). Significant differences were determined by Tukey’s post hoc test. F values for which p < 0.05 were regarded as statistically significant. Pearson’s correlation coefficient and regression analysis were used in order to evaluate the connection between behavioral measures, the antioxidant defence and lipid peroxidation. RESULTS: The beta-amyloid (1–42)-treated rats exhibited the following: decrease of the exploratory activity, the percentage of the time spent and the number of entries in the open arm within elevated plus-maze test and decrease of swimming time and increase of immobility time within forced swimming test. Administration of the methanolic extract significantly exhibited anxiolytic- and antidepressant-like effects and also antioxidant potential. CONCLUSIONS: Taken together, our results suggest that the methanolic extract ameliorates beta-amyloid (1–42)-induced anxiety and depression by attenuation of the oxidative stress in the rat amygdala.